Exploring the process of workplace ostracism leads to workplace deviance: The moderated mediation effect of coworker incivility - Wang, Le; Zhu, Lingfeng; Jin, Xiu (Acta psychologica, 2025)
With the awakening of diversified interests and the increasing complexity of workplace competition, ostracism and other undesirable workplace interactions have proliferated, considerably depleting employees' work and emotional resources. Workplace ostracism, a prevalent negative interpersonal dynamic, often depletes employees' resources and triggers deviant behaviors, causing significant organizational losses. This study examines how workplace ostracism influences employee deviance, focusing on moral disengagement as a mediator and coworker incivility as a moderator. To validate this model, we collected data from 303 employees from small- and medium-sized enterprises in China. The findings are threefold. First, workplace ostracism has a positive effect on employee workplace deviance through moral disengagement. Second, coworker incivility positively moderates the positive effect of workplace ostracism on employee workplace deviance. Third, coworker incivility moderates the effect of moral disengagement as the mediator of this pathway through which workplace ostracism positively affects workplace deviance. This study validates the negative aspects of workplace ostracism and moral disengagement, offers new insights regarding prevention of employee workplace deviance, and broadens the literature on the subject.